Pete the Cat Scaredy Cat! - Dean, Kim 1969; Dean, James, 1957- (New York, NY Harper, 2024)
"When Bob tells Pete the Cat a spooky, creepy, scary story about a monster, Pete is a little scared. The monster seems to be everywhere he looks! What will help Pete overcome his fear?"--
Guided reading level J.
114293
Keywords: Pete the Cat (Fictitious character) -- Juvenile fiction; Cats -- Juvenile fiction; Monsters -- Juvenile fiction; Fear -- Juvenile fiction